Reduced beta-amyloid sensitivity for platelet–monocyte aggregates in EDTA blood of alzheimer patients. (17th August 2017) - Defrancesco, Michaela; Marksteiner, Josef; Humpel, Christian
ABSTRACT: Alzheimer´s disease (AD) is a severe neurodegenerative brain disorder characterized by beta-amyloid plaques, Tau pathology, inflammation, neurodegeneration, and cerebrovascular dysfunction. Besides that, alterations in monocytes and platelets have been reported in the blood of Alzheimer patients. In the present study, we measured circulating levels of platelet–monocyte aggregates in EDTA blood of cognitively healthy participants and 40 AD patients, and examined their changes induced by stimulation with beta-amyloid peptides. We measured CD14, CD62P, and CD42a using fluorescence-activated cell scanning (FACS) analysis. Our data show that the levels of circulating monocyte–platelet aggregates were not different between healthy controls and AD patients. However, incubation with beta-amyloid-40, −42, and pyroglutamate-beta-amyloid increased the platelet–monocyte aggregation in healthy subjects, but not AD patients. Our data conclude that the interaction between monocytes and platelets is not altered in whole blood of AD patients, but their sensitivity toward beta-amyloid peptides is decreased. There might be a critical link between the interaction of platelets and monocytes in AD, which has to be explored in further studies.